Efektivitas Bimbingan Kelompok Berbasis Islami - Nadhifatuz Zulfa (Muwazah, 2017)
This study aims to knowing attitudes toward the double bourden of Muslim women who work (pretest and posttest) and the effectiveness of the implementation of Islamic-based group guidance to improve attitudes toward the double bourden of women. Location of research in Noyontaasari. Research approach is quantitative with experimental methods. The results showed that, the guidance of Islamic-based groups effectively increased attitudes toward the double bourden of woman Muslim workers. This is evident from the statistically significant wilcoxon test (probability <0.05). Therefore, there needs to be an Islamic-based group guidance service to improve attitudes toward women's double bourden, or to prevent the negative impact of Muslim women's double bourden on themselves and their families.